Analysis of Corn Farming For Gapoktan Farmers Nagori Sampuran (Case Study: Nagori Bah Sampuran, Jorlang Hataran District, Simalungun Regency) - Wahyunita Sitinjak; Ahmad Muliadi Harahap (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The title of the research is "Analysis of Corn Farming by Farmers of Gapoktan Bah Sampuran" Case Study: Nagori Bah Sampuran, Jorlang Hataran District, Simalungun Regency. The aims of this study were: To determine the effect (land area, seeds, fertilizers, pesticides, and labor) on maize farming by Gapoktan Bah Sampuran farmers, Tunas Jaya Poktan farmers, and Sejahterah, Nagori Bah Sampuran farmers. To find out the implementation of Farmers' Corn Farming in increasing the income of farmers of Gapoktan Bah Sampuran, Poktan Tunas Jaya, and Poktan Sejahtera, Nagori Bah Sampuran. This study aims to determine the role of the government in increasing corn farming income for farmers from Gapoktan Bah Sampuran, Poktan Tunas Jaya, and Poktan Sejahterah. The research area was determined that Nagori Bah Sampuran was the center of maize farming data production. The sample is the sampling method, the primary and secondary data methods, the primary from the questionnaire and direct interviews with the head of the respondent, secondary obtained by verified agencies. The analysis method R/C (Retum Cost Ratio) to know the comparison of income and costs, the results obtained the conclusion: The process of subsidized fertilizer assistance through RDKK in Nagori Bah Sampuran. Affects Educational Income, Experience, And Affects Production Land area, seeds, fertilizers, pesticides, labor, and capital. The results of the analysis are 1.97 starting from Production, Production Costs, Revenues, Net Income.